Effect of acute Zika virus infection on sperm and virus clearance in body fluids: a prospective observational study. Issue 11 (November 2017) - Joguet, Guillaume; Mansuy, Jean-Michel; Matusali, Giulia; Hamdi, Safouane; Walschaerts, Marie; Pavili, Lynda; Guyomard, Stefanie; Prisant, Nadia; Lamarre, Pierre; Dejucq-Rainsford, Nathalie; Pasquier, Christophe; Bujan, Louis
Summary: Background: Evidence of human sexual transmission during Zika virus emergence is a matter of concern, particularly in procreation, but to date, kinetics of seminal shedding and the effects of infection on human reproductive function have not been described. To investigate the effects of Zika virus infection on semen and clearance of Zika virus from semen and body fluids, we aimed to study a cohort of Zika virus-infected men. Methods: This prospective observational study recruited men presenting with acute Zika virus infection at Pointe-à-Pitre University Hospital in Guadeloupe, French Caribbean, where a Zika virus outbreak occurred between April and November, 2016. Blood, urine, and semen were collected at days 7, 11, 20, 30, 60, 90, and 120 after symptom onset, and semen characteristics, such as total sperm count, sperm motility, vitality, and morphology, and reproductive hormone concentrations, such as testosterone, inhibin, follicle-stimulating hormone, and luteinising hormone, were assessed. At days 7, 11, and 20, semen was processed to isolate motile spermatozoa. Zika virus RNA was detected by RT-PCR using whole blood, serum, urine, seminal plasma, semen cells, and motile spermatozoa fractions. Zika virus was isolated from different sperm fractions on Vero E6 cultures. Findings: 15 male volunteers (mean age 35 years [SD 5; range 25–44) with acute Zika virus infection and positive Zika virus RNA detection in blood or urine were enrolled. Total sperm count was decreased from median 119 × 10 6 spermatozoa (IQR 22–234) at day 7 to 45·2 × 10 6 (16·5–89·6) at day 30 and 70 × 10 6 (28·5–81·4) at day 60, respectively, after Zika virus infection. Inhibin values increased from 93·5 pg/mL (IQR 55–162) at day 7 to 150 pg/mL (78–209) at day 120 when total sperm count recovered. In motile spermatozoa obtained after density gradient separation, Zika virus RNA was found in three of 14 patients at day 7, four of 15 at day 11, and four of 15 at day 20, and replication-competent virus was found in the tested patient. Seminal shedding kinetics seemed heterogeneous among patients. Whole blood was the fluid most frequently positive for Zika virus RNA (62 of 92 samples) and three patients remained positive at day 120. Interpretation: Semen alterations early after acute Zika virus infection might affect fertility and could be explained by virus effects on the testis and epididymis. Frequency of shedding and high viral load in semen, together with the presence of replicative virus in a motile spermatozoa fraction, can lead to Zika virus transmission during sexual contact and assisted reproduction procedures. Whole blood seems to be the best specimen for Zika virus RNA detection, diagnosis, and follow-up. Funding: Agence de la Biomédecine/Agence Régionale de Santé de la Guadeloupe/Inserm-REACTing.